OPTIMALISASI LAYANAN BIMBINGAN KELOMPOK DAN KONSELING INDIVIDU DENGAN MENGGUNAKAN MEDIA POWER POINT SEBAGAI UPAYA PENINGKATAN KEBIASAAN BELAJAR SISWA KELAS IX-I DI SMP NEGERI 1 MATARAM - WARDIAH WARDIAH (Universitas Mahasaraswati Mataram, 2018)
There are many students experiencing learning problems, i.e. students hesitate to tell their problems to BK teachers in school. Besides teachers in doing guidance do not use media that can attract the attention of students, thus will have an impact on the decreasing of students’ science subject marks.This study aims to find out whether by optimizing the Group Guidance Services and Individual Counseling as well as the use of power point media can improve students' understanding of IX-I grade SMP Negeri 1 Mataram about the importance of learning habits, thereby affecting the increasing of the marks of Deuteronomy IPA students. This research is conducted for 6 months from July to December 2017 in class IX-I SMPN 1 Mataram in which 46 students are chosen to be the research subjects. The data retrieval technique uses observation, evaluation, and documentation. While the data analysis uses descriptive analysis qualitative and quantitative. Overall research results can be explained that for the achievement of percentage of the implementation of individual guidance and counseling services increased. In the first cycle with group guidance from 46 students who fill the questionnaire as many as 44 students with a mean of 79%. 10 of 46 students who are not yet optimal in understanding the meaning of study habits and the use of effective learning time, thus impacting the results of unfinished IPA quiz. Five students in the second cycle given Individual Counseling, the result turned out to increase to 100%. Improved understanding of study habits and the effective use of study time has an impact on the subsequent increase in IPA outcomes.